Analysis of the humoral and cellular response after the third COVID‐19 vaccination in patients with autoimmune hepatitis. (8th August 2022) - Hartl, Johannes; Rüther, Darius Ferenc; Duengelhoef, Paul Maria; Brehm, Thomas Theo; Steinmann, Silja; Weltzsch, Jan Philipp; Glaser, Fabian; Sterneck, Martina; Sebode, Marcial; Weiler‐Normann, Christina; Lütgehetmann, Marc; Schaub, Golda Melina; et al.
Abstract: Background & aims: To explore the humoral and T‐cell response to the third COVID‐19 vaccination in autoimmune hepatitis (AIH). Methods: Anti‐SARS‐CoV‐2 antibody titers were prospectively determined in 81 AIH patients and 53 healthy age‐ and sex‐matched controls >7 days (median 35) after the first COVID‐19 booster vaccination. The spike‐specific T‐cell response was assessed using an activation‐induced marker assay (AIM) in a subset of patients. Results: Median antibody levels were significantly lower in AIH compared to controls (10 908 vs. 25 000 AU/ml, p < .001), especially in AIH patients treated with MMF ( N = 14, 4542 AU/ml, p = .004) or steroids ( N = 27, 7326 AU/ml, p = .020). Also, 48% of AIH patients had antibody titers below the 10% percentile of the healthy controls (9194 AU/ml, p < .001). AIH patients had a high risk of failing to develop a spike‐specific T‐cell response (15/34 (44%) vs. 2/16 (12%), p = .05) and showed overall lower frequencies of spike‐specific CD4 + T cells (median: 0.074% vs 0.283; p = .01) after the booster vaccination compared to healthy individuals. In 34/81 patients, antibody titers before and after booster vaccination were available. In this subgroup, all patients but especially those without detectable/low antibodies titers (<100 AU/ml) after the second vaccination ( N = 11/34) showed a strong, 148‐fold increase. Conclusion: A third COVID‐19 vaccination efficiently boosts antibody levels and T‐cell responses in AIH patients and even seroconversion in patients with the absent immune response after two vaccinations, but to a lower level compared to controls. Therefore, we suggest routinely assessing antibody levels in AIH patients and offering additional booster vaccinations to those with suboptimal responses.